Strongyloides stercoralis disseminated infection in an HIV-infected adult. - Ambroise Le Pogam; Julien Lopinto; Adrien Pecriaux; Muriel Fartoukh; Juliette Guitard; Guillaume Voiriot (Public Library of Science (PLoS), 2020)
In this visual case of Strongyloides stercoralis disseminated infection with Enterobacteriaceae-related invasive infection, we demonstrated the in-host S. stercoralis circulation with DNA found in different fluids and specimens, but also in cerebrospinal fluid (CSF), supporting the role of migrant larvae in the Enterobacteriaceae-related invasive and central nervous system infection.